Discrimination of Chinese Herbal Medicine by Machine Olfaction - Dehan Luo; Yawen Shao (Institute of Advanced Engineering and Science, 2013)
“Small Sample Size” (SSS) problem would occur while using linear discriminant analysis (LDA) algorithm with traditional Fisher criterion if the within-class scatter matrix is singular. The combination of maximum scatter difference (MSD) criterion and LDA algorithm for solve SSS problem is described. It is employed to detect three kinds of Chinese herbal medicines from different growing areas by machine olfaction. Compared with PCA or PCA + LDA algorithm, the classification result was enhanced. It works out that only a few samples of Anhui Atractylodes are classified incorrectly, however, the classification rate reaches 97.8%. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1986